Pathogenic genomic alterations in Chinese pancreatic cancer patients and their therapeutical implications - Zhiming Zhao; Xiaomo Li; Fei Wang; Yong Xu; Si Liu; Quanli Han; Zhiying Yang; Weiwei Huang; Zhuzeng Yin; Qu Liu; Haidong Tan; Tonghui Ma; et al. (Cancer Medicine, 2023)
Abstract Background Approximately 90% of pancreatic ductal adenocarcinoma (PDAC) cases are driven by the untargetable non‐G12C KRAS mutations, and only a small subset of patients are eligible for FDA‐approved precision therapies. The practice of precision therapy in pancreatic cancer was limited by the paucity of targetable genetic alterations, especially in the Asian population. Methods To explore therapeutic targets in 499 Chinese PDAC patients, a deep sequencing panel (OncoPanscan™, Genetron health) was used to characterize somatic alterations including point mutations, indels, copy number alterations, gene fusions as well as pathogenic germline variants. Results We performed genomic profiling in 499 Chinese PDAC patients, which revealed somatic driver mutations in KRAS, TP53, CDKN2A, SMAD4, ARID1A, RNF43, and pathogenic germline variants (PGVs) in cancer predisposition genes including BRCA2, PALB2, and ATM. Overall, 20.4% of patients had targetable genomic alterations. About 8.4% of patients carried inactivating germline and somatic variants in BRCA1/2 and PALB2, which were susceptible to platinum and PARP inhibitors therapy. Patients with KRAS wild‐type disease and early‐onset pancreatic cancer (EOPC) harbored actionable mutations including BRAF, EGFR, ERBB2, and MAP2K1/2. Compared to PGV‐negative patients, PGV‐positive patients were younger and more likely to have a family history of cancer. Furthermore, PGVs in PALB2, BRCA2, and ATM were associated with high PDAC risk in the Chinese population. Conclusions Our results demonstrated that a genetic screen of actionable genomic variants could facilitate precision therapy and cancer risk reduction in pancreatic cancer patients of Asian ethnicity.